Dynamics of development of economic crime and combating crime in different regions of the world - Nestor, Nataliia; Lytvyn, Nataliia; Yarosh, Anna; Denysyuk, Stanislav; Rozhkova, Lyudmila (Revista San Gregorio, 2020)
The globalization of economic relations and the computerization of all spheres of life create favorable conditions for the commission of economic crimes, which is a problem not only of a national level but also an international one. The aim of the scientific article is to establish the level of economic crime in the world and certain countries, to determine its dynamics, to establish the causes of economic crimes in international relations, their consequences and to suggest ways to combat economic crime. Achieving this goal was carried out using the elemental and theoretical method, as well as using methods of comparison, analysis, generalization and analogy. The dynamics of economic crime at the international level is determined, which shows an increase in the commission of these crimes.